(untitled) (Indian Journal of Arid Horticulture, 2013)
Nagpur mandarin (Citrus reticulata Blanco) is the the region is 1000 mm. Maximum temperature range in 0 0 most valued member of Rutaceae family and enjoy summer is 43 to 47 C and thus the minimum temperature predominant position among fruit crops grown in the during winter is 4 to 6 C.